Training Residents in the Early Identification of Anxiety Disorders: Feasibility and Preliminary Efficacy of a Novel Training Program. (June 2019) - Mian, Nicholas D.; Carpenter, Aubrey L.; Pincus, Donna B.; Bair-Merritt, Megan; Perrin, Ellen C.
Pediatric anxiety disorders are highly prevalent, but tend to go undetected as pediatricians often lack relevant training. We developed a brief, video-based training program for pediatric residents aimed at improving early identification of child anxiety disorders. The novel training was completed in a group-based format or via an online, asynchronous training program. Pediatric residents from 2 residency programs (n = 63) participated and completed pre- and posttraining surveys evaluating attitudes about previous training, knowledge about child anxiety, perceived evaluation skills, and responses to clinical vignettes. Most residents (81%) reported they did not receive enough prior training in the presentation of anxiety disorders in young children. Residents' knowledge and perceived evaluation skills increased posttraining. On the vignette-based assessment, residents demonstrated increased sensitivity with regard to interference, diagnosis, and referral urgency. Despite some challenges with participation, results provide preliminary evidence that brief training programs could be an effective way to improve resident education.